If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 156 = (6w + -9) Reorder the terms: 156 = (-9 + 6w) Remove parenthesis around (-9 + 6w) 156 = -9 + 6w Solving 156 = -9 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 156 + -6w = -9 + 6w + -6w Combine like terms: 6w + -6w = 0 156 + -6w = -9 + 0 156 + -6w = -9 Add '-156' to each side of the equation. 156 + -156 + -6w = -9 + -156 Combine like terms: 156 + -156 = 0 0 + -6w = -9 + -156 -6w = -9 + -156 Combine like terms: -9 + -156 = -165 -6w = -165 Divide each side by '-6'. w = 27.5 Simplifying w = 27.5
| 2z^2=30+7z | | 6ab-8bc=4bd | | 5u+2v= | | -9d^2=-405 | | 2xy-xz=4 | | 8*8=8 | | 11/4(5/3x-7/4) | | 8*8=111 | | 8*5=70 | | x/-3+12 | | 6u+v=18 | | (2+4)*5+10-18+7+5*(7+1)+4*0= | | 2t/3=4/9 | | 6c+3u=36 | | (3b-c-4)=2 | | 81x-8=1 | | 81x-=1 | | 4.6w+0.19=5539 | | 4x-y+8=2 | | 26=-3x+5 | | (4x-y+8)=2 | | 3x^4+8x^3-15x-40=0 | | 3(x+1)=y | | .018c=36 | | f(x)=(x^2+4x+4)-3 | | .4y=48 | | .06b=24 | | Y-x+1=1 | | .002t=6 | | .7a=490 | | -73=5n+78 | | (y-x+1)=1 |